Internal Control System : Pencegahan Fraud Dalam Pengelolaan Keuangan Desa (Studi Kasus Pada Desa Karangsono Kecamatan Bangsalsari Kabupaten Jember) - Laily Chudriyah AM; Yulinartati; Suwarno (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine whether or not fraud occurs in financial management in Karangsono village and how the internal control system exists in the village. The research was conducted using a descriptive method with a qualitative approach. The subjects in this study were conducted by interviewing 5 village officials and observing the object under study, namely in Karangsono Village. The technique used in this research is starting from data collection, data presentation, and data retrieval. The results of this study are internal control, apparatus competence, good individual morality, which greatly influences the prevention of fraud that will occur in village financial management.